Negosiasi dan kerja tripartit dalam penanganan krisis komunikasi perusahaan: tinjauan pada kinerja csr - Rihfenti Ernayani; Rustandi Rustandi; Pandji Santosa; Thomas Bustomi; Tati Sarihati (Jurnal Komunikasi Profesional, 2022)
An unexpected event that has the potential to cause turmoil and changes in an environment is referred to as a crisis. The emergence of a crisis in the organization can damage the image and reputation of the company. If a crisis arises in a company and is publicized, it can lead to a bad perception of the company, organization or individual. So that it is necessary to have a public relations role to formulate communication program planning procedures in solving crises. However, if a settlement between the worker and the company cannot be resolved, then a mediator is needed or called the Tripartite model. The purpose of this study was to determine the tripartite model in handling corporate communication crises in terms of the performance of Corporate Social Responsibility. The method used in this research is phenomenology, where the informant in this study is the company's public relations officer. The conclusion of this study shows that the involvement of third parties (tripartite model) is not carried out by companies that have done to the environment and the community through introduction to the environment so that they can determine the Corporate Social Responsibility program appropriately and handle crisis communication well.